2020
DOI: 10.4067/s0717-95022020000601651
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Stature Estimation from Adult Lumbar Vertebrae in a Thai Population Based on Image Analysis

Abstract: Although molecular techniques evolved considerably in last years, anthropological methods of assessing skeletal remains, continues to be an important tool in the identification process in medico legal investigations. The objective of this study was to develop a discriminant function equation for estimating sex and stature using several measurements of lumbar vertebrae in a Thai population. We studied 150 lumbar columns (75 male and 75 female) age range of 22 to 89 years from the Forensic Osteology Research Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 15 publications
(15 reference statements)
1
23
0
1
Order By: Relevance
“…19 Suwanlikhid et al used dry bone and image analysis which had an accuracy of 81.8% from the discriminant equation of L1. 18 The results of using deep-learning image classification on dry bone images in this study were satisfactory. Similar to other studies that used different types of medical images to determine sex, the utilization of CT-scanned pelvic images had accuracies between 94% and 98.5%, whereas the lumbar spine X-ray images achieved an accuracy of 98%, and hand radiograph was able to correctly determine sex with an accuracy of 98%.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…19 Suwanlikhid et al used dry bone and image analysis which had an accuracy of 81.8% from the discriminant equation of L1. 18 The results of using deep-learning image classification on dry bone images in this study were satisfactory. Similar to other studies that used different types of medical images to determine sex, the utilization of CT-scanned pelvic images had accuracies between 94% and 98.5%, whereas the lumbar spine X-ray images achieved an accuracy of 98%, and hand radiograph was able to correctly determine sex with an accuracy of 98%.…”
Section: Discussionmentioning
confidence: 54%
“…31 The mean age of the subjects is similar to a previous study that used CT images and 2D dry bone images. [17][18][19][20] The previous studies showed that age did not impact the results of sex determination from the vertebral body. Using dry bone is useful in burned events that causes bones to be fragmented.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations